2001
DOI: 10.1038/83829
|View full text |Cite
|
Sign up to set email alerts
|

A thyroid hormone receptor that is required for the development of green cone photoreceptors

Abstract: Color vision is facilitated by distinct populations of cone photoreceptors in the retina. In rodents, cones expressing different opsin photopigments are sensitive to middle (M, 'green') and short (S, 'blue') wavelengths, and are differentially distributed across the retina. The mechanisms that control which opsin is expressed in a particular cone are poorly understood, but previous in vitro studies implicated thyroid hormone in cone differentiation. Thyroid hormone receptor beta 2 (TR beta 2) is a ligand-activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

30
466
6
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 498 publications
(514 citation statements)
references
References 26 publications
30
466
6
1
Order By: Relevance
“…The thyroid hormone receptor Trβ2, a splice variant of the thyroid hormone receptor B (Thrb) gene, is implicated in photoreceptor development in chick and mouse, based on its expression in retinal progenitor cells and developing photoreceptors. In mouse eyes, expression of Trβ2 begins about E16, peaks around E18 as cone photoreceptors begin differentiating, then decreases (Ng et al, 2001;Yanagi et al, 2002), but the expression is uniform across the retina (Ng et al, 2001;Roberts et al, 2005;Roberts et al, 2006). However, during the time M-cones are developing, its ligand TH becomes distributed in a gradient with higher concentrations in the dorsal than ventral retina [ (Roberts et al, 2006); Figure 2B].…”
Section: Trβ2 Is a Positive Regulator For M-conesmentioning
confidence: 99%
See 2 more Smart Citations
“…The thyroid hormone receptor Trβ2, a splice variant of the thyroid hormone receptor B (Thrb) gene, is implicated in photoreceptor development in chick and mouse, based on its expression in retinal progenitor cells and developing photoreceptors. In mouse eyes, expression of Trβ2 begins about E16, peaks around E18 as cone photoreceptors begin differentiating, then decreases (Ng et al, 2001;Yanagi et al, 2002), but the expression is uniform across the retina (Ng et al, 2001;Roberts et al, 2005;Roberts et al, 2006). However, during the time M-cones are developing, its ligand TH becomes distributed in a gradient with higher concentrations in the dorsal than ventral retina [ (Roberts et al, 2006); Figure 2B].…”
Section: Trβ2 Is a Positive Regulator For M-conesmentioning
confidence: 99%
“…These results showed that Trβ2 induced M-opsin expression and concurrently inhibited S-cone production in a ligand-dependent manner. Knockout of the photoreceptor-specific Trβ2 isoform of the Thrb gene converted all cones to the S-phenotype, resulting in loss of both M-opsin expression and the S-cone gradient in vivo (Ng et al, 2001). This phenotype is also reproduced in a mouse with a knockin mutation in the DNA binding domain of Thrb that abolishes specific DNA sequence binding without affecting ligand binding or cofactor interactions (Shibusawa et al, 2003).…”
Section: Trβ2 Is a Positive Regulator For M-conesmentioning
confidence: 99%
See 1 more Smart Citation
“…In mice, at least two nuclear receptor isoforms, TR␤1 and TR␤2, are encoded by a TR␤ gene locus. When the TR␤2 isoform is deleted, S opsin repression in the dorsal cones is lost and M opsin transcription is abolished in all cones (Ng et al, 2001;Shibusawa et al, 2003). S opsin is transcribed early during the embryonic period in mouse and humans, but M opsin is expressed days or weeks later as the cone cell matures (Szél et al, 1993;Chen et al, 1994;Xiao and Hendrickson, 2000;Cornish et al, 2004a).…”
Section: Introductionmentioning
confidence: 99%
“…(Akagi, et al, 2004, Brown, et al, 1998, Brown, et al, 2001, Hojo, et al, 2000, Kanekar, et al, 1997, Marquardt and Gruss, 2002, Moore, et al, 2002, Morrow, et al, 1999, Yan and Wang, 1998 Several transcription factors are clearly essential for photoreceptor development, and their mutations cause retinal degenerations: NRL, CRX, Otx2, Trβ2 (thyroid hormone receptor β2), and NR2E3. (Bessant, et al, 1999, DeAngelis, et al, 2002, Freund, et al, 1997, Haider, et al, 2000, Haider, et al, 2001, Martinez-Gimeno, et al, 2001, Ng, et al, 2001, Nishida, et al, 2003, Swain, et al, 1997 However, our knowledge of the interactions of these cell-specific proteins with each other and upstream signal transduction proteins remains sparse. We do not know how this pool of cell-specific transcription factors interacts with the pool of ubiquitous proteins, which include the general transcription machinery and epigenetic regulators of chromatin/DNA structure.…”
Section: Introductionmentioning
confidence: 99%